Introduction – Design as Semiosis - Frangopoulos, Miltos; Zantides, Evripides (My University, 2018)
Ever since Roland Barthes, back in the mid-1950s, commented on the ideological myths infusing the design of the new Citroen DS or of the cover of Paris Match, the fates of design and semiotics have been inextricably entwined. From ‘les trente glorieuses’ of expanding mass production and mass consumption, however, to the current trend for customization, sustainable design, collaborative and participatory design, parametric design combined with 3D printing, we discern a reorientation from a use-centered, scientific design to a user-centered design driven by post-materialism and intuitive ‘design thinking’. At the same time, semioticians moved from unraveling the mystifying effects of design upon a beguiled mass-consumer to championing a more expanded understanding of design as a fundamental dimension of the human activity of meaning-making, world-making and identity-making.
Keywords: Semiosis; Design